Do gender-related differences exist in Spanish entrepreneurial activity? - Federico Pablo-Marti; Antonio García-Tabuenca; José Luis Crespo-Espert (European Regional Science Association (ERSA), 2011)
The participation of women in entrepreneurial activity forty years ago was virtually an exception. However, nowadays this is an important economic and social phenomenon, with an outstanding impact on the dynamics of both advanced and emerging economies. This is significant not only from a quantitative viewpoint. The fact that female personal features, motives and managerial methods differ from those of men gives a new and interesting perspective -which is still subject to debate- to the analysis regarding training and consolidation of enterprises. Gender-related differences can be the vehicle to introduce innovative aspects that could be influential in the uncertain and changing economic environment after the current crises, particularly in those fields where business output is related to the quality of life. Adopting a previous regional model as a basis of study, we analyse in this work the characteristics that differentiate entrepreneurial women in Spain on the grounds of data collected from an own drafted survey regarding the entrepreneurial activity (607 complete questionnaires) carried out in 2009. The results obtained indicate the coexistence of two different types of entrepreneurial women. The first group gathers those women whose enterprises show, generally speaking, a similar sectoral distribution to that of the whole productive fabric, although with a slight tendency to be more present in services activities. Their characteristics and attitudes are, in general, quite similar to those registered among entrepreneurial men and many of these women come from entrepreneurial families. The second group is mainly made up of entrepreneurial women -frequently with family burdens and low qualified- devoted to services, particularly personal services and retail trade. Technological and managerial characteristics of companies managed by the entrepreneurial women belonging to this group differ substantially from the average of the economy, with a much more traditional and less innovative profile.
Keywords: 330